THE DIVERSITY OF LEPIDOPTERA (INSECTA) IN MOUNT KENDENG AND MOUNT BOTOL, GUNUNG HALIMUN NATIONAL PARK, WEST JAVA - Tri Atmowidi; Taruni Sri Prawasti; Nawangsari Sugiri; Yana Kurniawan (Research Center for Biology-Indonesian Institute of Sciences, 2001)
-